Dampak Pernikahan Dini terhadap Pendidikan Anak di Desa Banjarrejo Kecamatan Batanghari Kabupaten Lampung Timur - Heni Yuliana Wati (LPPM Politeknik Pratama, 2024)
Marriage is a great institution to bind two people of the opposite sex into one family bond. This research aims to determine the impact of early marriage on children's education in Banjarrejo Village. This research uses data collection methods, namely interviews, documentation, observation and triangulation. Then observations were made on the children of young couples. The type of research used is field research, and the nature of this research is descriptive qualitative. Thus, research results can be obtained that residents of Banjarrejo Village who marry at an early age are due to low economic factors, low education, psychological impacts, so that these factors have an impact on children's education.